Assessing Corn Response to Cover Crops and Nitrogen Fertilization in a No-Till, Three-Year Rotation in Northeast Kansas - Jessica Grünberg; Alexis Correira; Kraig L. Roozeboom; DeAnn R. Presley; Peter J. Tomlinson (Kansas Agricultural Experiment Station Research Reports, 2023)
A long-term cover crop experiment was established in 2007 at Ashland Bottoms near Manhattan, KS, to determine the effect of cover crops and nitrogen (N) rates on subsequent corn growth and yield in a wheat-corn-soybean rotation. Treatments included chemical fallow, double crop soybean, different cover crops (cereal rye,crimson clover, a mix of cereal rye and crimson clover, and a diverse mix of seven species) planted in late summer after wheat harvest, and five N rates (0, 40, 80, 160, and 240 lb/acre) applied to the subsequent corn crop. Yield responded differently to N rate depending on cover crop treatment and year. In both 2021 and 2022, corn after chemical fallow and double crop soybeans maximized yields at 80 lb N/acre, but corn following cereal rye and the cereal rye-crimson clover mix needed 160 to 240 lb N/acre to maximize yield. Nitrogen fertilizer replacement values (NFRV) were negative for most cover crop treatments, indicating immobilization of soil N. The double crop soybean NFRV had the least negative value. Overall, N availability for uptake by the subsequent corn crop was reduced by cover crop treatments compared to the check. However, soil water used by the cover crops likely also contributed to corn yield reductions and confounded with NFRV estimations.
Keywords: cover crop; nitrogen; corn; no-till